2021
DOI: 10.1371/journal.ppat.1009476
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal-epithelial LSD1 controls goblet cell maturation and effector responses required for gut immunity to bacterial and helminth infection

Abstract: Infectious and inflammatory diseases in the intestine remain a serious threat for patients world-wide. Reprogramming of the intestinal epithelium towards a protective effector state is important to manage inflammation and immunity and can be therapeutically targeted. The role of epigenetic regulatory enzymes within these processes is not yet defined. Here, we use a mouse model that has an intestinal-epithelial specific deletion of the histone demethylase Lsd1 (cKO mice), which maintains the epithelium in a fix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
14
0
2
Order By: Relevance
“…S5C). In accordance with our previous work ( 18 ), confocal staining confirmed that MUC2 was induced by IL-13 (Fig. 2, D and F), and that RELMβ was more strongly induced by IL-22 (Fig.…”
Section: Resultssupporting
confidence: 93%
“…S5C). In accordance with our previous work ( 18 ), confocal staining confirmed that MUC2 was induced by IL-13 (Fig. 2, D and F), and that RELMβ was more strongly induced by IL-22 (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Goblet cells found in the intestine secrete mucus that acts as an immune-defensive barrier against microbes and parasites that may invade the intestine during food ingestion (Parmar et al 2021 ). Many studies have reported that goblet cells are highly affected by Eimeria infection (Dkhil et al 2013 ; Kim et al 1996 ) In the current study, histological sections of jejuna of E. papillata -infected mice observed on day 5 postinfection showed a reduction in the number of goblet cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find differences in the transcript levels for secretory cell markers in organoids, it is possible that these changes may be visible at a protein level, as observed in zebrafish. In addition, SI organoids do not show elevated numbers of goblet cells under normal sterile growth conditions, thus the addition of inducers of goblet cell differentiation, such as type 2 cytokines or Notch inhibitors 64 would be needed to potentially visualize its regulation by IL-10. Nevertheless, our results from SI organoids match previous findings from single-cell transcriptomic analysis of mouse intestinal organoids, which showed an increased Rgcc expression after IL-10 treatments.…”
Section: Discussionmentioning
confidence: 99%